Porous metal-organic frameworks for sorption of volatile organic compounds - Ndamyabera, Christophe Adrien (Department of Chemistry, 2021)
Metal-organic frameworks (MOFs) present potential for various applications such as gas sorption, gas storage, sensing, drug delivery, and catalysis. This attracts researchers to design and synthesize MOFs that can respond to a specific application. In this thesis, mixed ligands 34pba and 44pba ligands (34pba = 3-(4-pyridyl)benzoate, and 44pba = 4-(4-pyridyl)benzoate) and Co2+ metal salts were used to synthesize porous MOFs {[Co(34pba)(44pba)]·DMF}n (1) and {[Co(34pba)(44pba)]·(C3H6O)}n (2), with DMF = N,N'-dimethylformamide and C3H6O = acetone through solvothermal reaction. These two relate to each other through hinge-like expansion or contraction of the guest-accessible void. The use of Zn2+ as a metal ion led to an isostructural MOFs [Zn(34pba)(44pba)]·DMF}n (3) of 1. Using 34pba as a single ligand and Cu2+ as the metal ion led to the formation of a 2D [(Cu(34pba)2]·DMF) (4) while a little variation of solvent mixture resulted in a 3D {[CuCl2(34pba)2]∙solvent}n (7) structures. The functionalized ligands 44paba and 34paba (34paba = 3-(pyridyn-4-ylmethyl)aminobenzoate, 44paba = 4-(pyridyn-4- ylmethyl)aminobenzoate) were used with Cu2+ centre to prepare [Cu(44paba)·(H2O)·(DMF)]n (5) and {[Cu3(34paba)5(H2O)2]·(DMF)2}n (6), both of which are 1D structures. The activated MOFs 1d and 3d from (1 and 2) were used for the adsorption of volatile organic compounds (VOCs) and gases. In all tested guest molecules, there was higher sorption capacity in 1d which could be attributed to some gate opening process occurring which does not occur in 3d. Some effects responding to the sorption such as the change of colour in 1d were characterized. This colour change may be associated with the d-d, metal to ligand charge transfer, or π to π* transitions in coordination complex. Crystal structures and their stability, sorption properties and selectivity were characterized by single crystal X-ray diffraction, thermogravimetric analysis, differential scanning, hot stage microscopy, powder X-ray diffraction, infrared spectroscopy, and proton viii nuclear magnetic resonance (1H NMR) analysis. This thesis also reports the effect of methanol on discrete complexes of cis-dichloro-bis(ethylenediamine)cobalt(III) chloride (Coen) that led to the formation of a new crystal structure upon the removal of the water of hydration. The lattice energies calculated prove that Coen is more stable to allow a quick reversible sorption.